Personal, Biomechanical, Organizational and Psychosocial Risk Factors for Neck Disorders in a Working Population. Issue 2 (3rd October 2014) - Petit, Audrey; Ha, Catherine; Bodin, Julie; Parot‐Schinkel, Elsa; Ramond, Aline; Leclerc, Annette; Imbernon, Ellen; Roquelaure, Yves
Abstract : Personal, Biomechanical, Organizational and Psychosocial Risk Factors for Neck Disorders in a Working Population: Audrey PETIT, et al . LUNAM University, Laboratory of Ergonomics and Epidemiology in Occupational health, (LEEST), University of Angers, Faculty of Medicine, France— Objectives: The aim of the study was to assess both personal and occupational risk factors for non‐specific neck disorder (ND) in a representative working population characterized by various levels of exposure to work‐related constraints. ND during the preceding 7 days was assessed in 3, 710 workers surveyed by 83 occupational physicians between 2002 and 2005. Personal risk factors and work exposure were assessed by a standardized examination and a self‐administered questionnaire. Associations between ND and personal and occupational factors were analyzed using logistic regression modeling separately in men and in women. Results: The personal risk factors for ND were age (OR for 1‐year increment 1.02, 95% CI 1.01 to 1.03 in men and 1.03 [1.01−1.04] in women) and previous history of arthritis disease (OR 2.39 [1.17−4.91] in men and 3.95 [1.92−8.12] in women). The risk of ND increased with previous history or upper limb musculoskeletal disorders in men (OR 1.58 [1.17−2.13]) and decreased with BMI in women (OR for 1‐kg/m 2 increment 0.96, [0.93−0.99]). The work‐related risk factors of ND were sustained or repeated arm abduction (OR 2.08 [1.35−3.21] in men and 2.22 [1.27−3.86] in women) and neck flexion (OR 1.64 [1.26−2.12] in women). Work pace dependent on customers (OR 1.42 [1.10−1.83]) and psychological demand of the task (OR 1.49 [1.15−1.92]) increased the risk of ND in men. Work pace dependent on quantified targets (OR 1.37 [1.05−1.79]) and low supervisor support (OR 1.68 [1.30−2.17] ) increased the risk of ND in women. This study highlighted the multifactorial nature of ND.